The importance of academic leagues in the pandemic contexto of COVID-19: na experience report (Research, Society and Development, 2022)
This study aims to report the experience of nursing students about the importance of academic leagues during the COVID-19 pandemic, seeking to analyze their perception of activities performed remotely and what their implications are. This is an experience report with a qualitative approach, developed through an electronic form for data collection and analyzed using Bardin's theory of analysis. Eighteen forms were returned and from these, data were collected regarding the importance of the academic league in the pandemic context. From the form, 13 students consider league meetings to be a positive experience. It was also observed that the pandemic implied some impasses for most ligands (67%), as they reported that they had difficulty joining a league, showing that the existence of the pandemic significantly affected the entry of academics into leagues. The form also addressed the positive aspects provided by the league during the pandemic and for this question, most students reported sharing knowledge, encouraging research, participating in online events, socialization and scientific production. Therefore, it is noted that despite the pandemic, the league plays an important role today, maintaining its goals aimed at teaching, research and extension, offering students new teaching formats in the scenario we are living.